1981
DOI: 10.1246/bcsj.54.687
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced Phase Transition and Compressive Behavior of Substituted Adamantanes

Abstract: The compressive behavior of adamantane and its secondary monosubstituted derivatives; adamantanone, 2-methyladamantane, and 2-bromoadamantane was measured at various temperatures in a piston-cylinder apparatus. A first-order solid-solid phase transition was found under pressure in each system. The transition pressures, the equilibrium pressures, the volume changes, and the entropy changes for the transition were determined. The compression data for the low pressure phases were fitted to an equation of the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
21
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 10 publications
8
21
0
Order By: Relevance
“…, are close to the volume change at the ordered to orientationally disordered transition for some adamantane derivatives, [46][47][48] thus reinforcing the orientationally ordered character of phase I for the case here studied. Moreover, the changes of the thermodynamic properties at the melting process do not correlate with the relationships established for orientationally disordered phases.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…, are close to the volume change at the ordered to orientationally disordered transition for some adamantane derivatives, [46][47][48] thus reinforcing the orientationally ordered character of phase I for the case here studied. Moreover, the changes of the thermodynamic properties at the melting process do not correlate with the relationships established for orientationally disordered phases.…”
Section: Resultssupporting
confidence: 77%
“…Although the number of studies concerning 2-X-adamantane derivatives is less extensive, detailed polymorphic studies have also been reported. [15][16][17][18][19][20][21][22] The phase behavior of the 1-X adamantane compounds varies according to the substituent.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] As for the latter, with C 2v symmetry, the literature studies are scarce and, concerning the polymorphic behavior as a function of temperature and pressure, there are some hints but sometimes contradictory. [19][20][21][22][23][24][25][26][27][28][29][30][31] Among the 2-X-adamantane derivatives, 2-O-adamantane (2-adamantanone, C 10 H 14 O, hereinafter called 2O-A) has probably been the most studied in the OD phase. The polymorphic behavior of this compound has been described as follows.…”
Section: Introductionmentioning
confidence: 99%
“…205 K. 19,20,30,31 A large number of works has been published concerning the orientational disorder of the OD phase, whereas the low-temperature phase was found to be perfectly ordered through NMR studies. [19][20][21][22][23][24][25][26][27][28][29][30][31] Nevertheless, recent dielectric spectroscopy analyses and X-ray diffraction have shown that a statistical intrinsic disorder concerning the site occupancy of the oxygen atom along different sites giving rise to large-angle molecular rotations associated to time-average fluctuations of the molecular dipole exist. 24 As a consequence of such a disorder the dielectric spectra showed the universal features of glass-like materials in which αand β-relaxation processes appear.…”
Section: Introductionmentioning
confidence: 99%
“…The order-disorder transitions in 1-substituted adamantanes (C10H15R; R = 1-COOH ( l o ) , 1-NH3+Cl-(1 l ) , 1-CN (12), 1-C1 (16), 1-Br (16)) have been examined. Little work has been done on 2-substituted derivatives (13,17,18), and as part of a study of the phase-transition behaviour of adamantane derivatives, we report here the results of an investigation of the order-disorder transitions in 2-chloroadamantane, 2-CloH15C1, by differential scanning calorimetry (DSC), and variable-temperature FT-IR and Raman spectros-COPY.…”
Section: Introductionmentioning
confidence: 99%